Child Sexual Abuse by Religious Authority Figures in Germany and Israel: The Experiences and Perceptions of Adult Survivors - Lusky-Weisrose, Efrat (Journal of interpersonal violence, 2022)
The current study is based on an in-depth thematic analysis of 20 interviews with German and Israeli adult survivors of child sexual abuse (CSA) by religious authority figures (RAF). This paper aims to explore survivors? experiences within the Jewish ultra-Orthodox and Christian communities, as well as to draw comparisons between the abusive structures and disclosure in these two contexts. The results point to the complexity of CSA by RAF, which is embedded in the survivors? perceptions of themselves as emotionally and cognitively captured by the perpetrators who are a symbol of a parent or God and faith. The participants expressed great concern regarding disclosing the abuse against the backdrop of familial, cultural, and community inhibitors, such as fear of social stigmatization, inability to recognize the abuse, and the taboo of sexuality discourse. The survivors? traumatic experiences were intensified in light of negative social responses to disclosure and encounters with insensitive officials. A comparison of the cultures revealed differences regarding the nature of community life and educational institutions, which may have shaped the disclosure and recognition of the abuse. The study highlights the importance of comparative follow-up studies related to this phenomenon in order to examine its universal and unique cultural contexts.